PENGARUH PROFITABILITAS, MEKANISME PEMANTAUAN DAN FINANCIAL DISTRESS TERHADAP MANAJEMEN LABA - Carolina Reni Damayanti; Warsito Kawedar (Diponegoro Journal of Accounting, 2018)
This study aims to examine the effect of profitability, monitoring mechanism and financial distress on earnings management. Profitability is measured by return on asset (ROA), monitoring mechanism is measured by leverage, and financial distress is measured by Altman Z-score. The population of this study are all go public companies listed in Indonesia Stock Exchange from 2013 until 2015. The number of samples in this study are 267 companies. The result of the analysis of this study indicates that profitability has no significant effect on earnings management, while monitoring mechanism and financial distress have a significant effects on earning management.